Sweden : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues paper discusses capital and liquidity regulations in Sweden. It recaps the recent debates on capital and liquidity buffers, and discusses a way to consider appropriate levels of capital and liquidity buffers in the case of Sweden. The paper estimates the government's contingent liabilities from banks by different capital and liquidity levels. Also examined are options for Sweden in case the authorities face constraints to set buffers at their desirable levels.